PERCEPTIONS ABOUT BLOOD DONATION AMONG ARMY PERSONNEL - Alam, Maqbool; Talha, Mohammad; Ahmed, Shafiq (Pakistan Armed Forces Medical Journal, 2006)
Objective: There is little literature on the public attitudes towards blood safety and blood donation in Pakistan. The purpose of study was to identify the misconceptions, beliefs and fears about blood donation among army personnel so that appropriate strategies can be adopted for the recruitment of voluntary non-remunerated blood donors in future. Place and Duration of Study: This cross sectional descriptive study was carried out at 123 (I) Fd Amb from July 2004 to Dec 2004. Subjects and Methods: A self-administered questionnaire and face-to-face interview on the various aspect of blood donation were used for data collection from each individual. A total of 200 army personnel participated in the study. Results: Out of 200 individuals, 41 (20.5%) were donors and 159 (79.5%) were non-donors. One hundred and eighty nine (94.5%) including donors and non-donors replied that a person more than 45 years of age could not donate blood. Out of 159 non-donors, 137 (86.16%) were of the opinion that blood donor should be of >60 Kg of weight. One hundred and seven (67.30%) of the non-donors answered that one can donate blood once a year. One hundred and forty five (91.20%) non-donors did not know amount of blood extracted during each donation. Out of 159 non-donors, 78 (49.06%) replied that they were not approached by anybody for blood donation. Out of 200 donors and non-donors, 105 (52.5%) revealed that extra leave could be the major incentive for blood donation. Conclusion: This study revealed the misconceptions regarding blood donation among army personnel. This needs education and motivation through dissemination of information regarding blood donation particularly by medical staff.